Implementasi Multikultural Budaya Dalam Interaksi Sosial Siswa Di Sekolah Dasar - Sunaryati, Titin; Aulia, Najwa Ramadhani; Yuliyanti, Lina; Maulana, Ayu Sintia; Tasya, Ainun (Innovative: Journal Of Social Science Research, 2025)
Multicultural education in schools is an important aspect of student development that can be improved through school habituation and culture. The study identifies the supporting and inhibiting factors in the implementation of character education, highlighting the differences between the current findings and previous research. The results show that despite the enthusiasm of students and the support of teachers and parents, challenges such as differences in teachers' abilities, lack of facilities, and variations in students' abilities are still obstacles. Significant supporting factors include the school's commitment to providing adequate infrastructure and training for teachers. The discussion emphasized the importance of collaboration between all relevant parties to create an environment conducive to the development of students' character. This research provides new insights into how school culture can be optimized to achieve character education goals effectively.